Social Media, Misinformation and Covid-19 - Desai, Bhavana (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Social media has come as a boon, and as curse of spreading false news. Fake news has always been on the horizon even earlier. Only difference is that the fake news in earlier times was more risky and dangerous. Because in those times, identifying the fake news was not only difficult but propagating about it was also difficult. In these times, even though we have fake news the controlling measures are better and convincing people about them easy. With Covid-19, the pandemic in a century, people saw the havoc fake news can play. The paper defines, classifies Fake news. It discusses all the measures taken by various social media to address this issue. It also broadly gives an overview of the technical measures taken to address the issue.